2004
DOI: 10.1016/j.chembiol.2004.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Biosynthesis of Geldanamycin Analogs for Hsp90 Inhibition

Abstract: Geldanamycin, a polyketide natural product, is of significant interest for development of new anticancer drugs that target the protein chaperone Hsp90. While the chemically reactive groups of geldanamycin have been exploited to make a number of synthetic analogs, including 17-allylamino-17-demethoxy geldanamycin (17-AAG), currently in clinical evaluation, the "inert" groups of the molecule remain unexplored for structure-activity relationships. We have used genetic engineering of the geldanamycin polyketide sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
88
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(96 citation statements)
references
References 50 publications
(11 reference statements)
3
88
0
Order By: Relevance
“…In a more recent study, a conserved hydrophobic motif in HSP90 β strand has been reported to regulate the secretion and function of HSP90 (30). Thus, the presence of detergent can influence 17AAG binding to HSP90, potentially contributing to the poor correlation between binding affinity and cytotoxicity (31,32) or to the potency gap between biochemical binding and Her2 degradation (33). We tested detergent by itself and found that 17AAG can significantly bind to detergent micelles.…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent study, a conserved hydrophobic motif in HSP90 β strand has been reported to regulate the secretion and function of HSP90 (30). Thus, the presence of detergent can influence 17AAG binding to HSP90, potentially contributing to the poor correlation between binding affinity and cytotoxicity (31,32) or to the potency gap between biochemical binding and Her2 degradation (33). We tested detergent by itself and found that 17AAG can significantly bind to detergent micelles.…”
Section: Discussionmentioning
confidence: 99%
“…geldanus NRRL 3602 [15]. The genetic manipulation of the gene or domain of the GDM biosynthetic gene cluster is helpful for understanding the biosynthesis process, and creates new analogues of GDM [16,18].…”
Section: Introductionmentioning
confidence: 99%
“…79,80 Other geldanamycin analogs with improved therapeutic properties have been developed by Professor Hutchinson and collaborators by engineering its biosynthesis gene cluster. 81,82 We planned to generate novel streptolydigin derivatives, using combinatorial biosynthetic approaches, in an attempt to obtain better cytotoxic or antibiotic compounds. Structurally, streptolydigin is a polyketide/non-ribosomal peptide that belongs to the tetramic acids family.…”
Section: Novel Glycosylated Analogs Of Steffimycinmentioning
confidence: 99%